2002
DOI: 10.1034/j.1601-0825.2002.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐related oral disease epidemiology among women: year 2000 update

Abstract: Future oral epidemiology research efforts in Africa should focus on the potential role of OC as sentinel marker of HIV infection and disease progression, to improve detection and prevention of selected opportunistic illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…It has been proposed that oral lesions may be utilized as surrogate markers of disease progression in adults in the developing world, in the absence of laboratory markers (Shiboski, 2002). Only one longitudinal study from a resourcepoor country showed a more rapid progression to AIDS in adults with OHL and/or OC (Ramírez-Amador et al, 1996).…”
Section: Orofacial Disease May Predict Hiv Disease Progression In Adumentioning
confidence: 99%
“…It has been proposed that oral lesions may be utilized as surrogate markers of disease progression in adults in the developing world, in the absence of laboratory markers (Shiboski, 2002). Only one longitudinal study from a resourcepoor country showed a more rapid progression to AIDS in adults with OHL and/or OC (Ramírez-Amador et al, 1996).…”
Section: Orofacial Disease May Predict Hiv Disease Progression In Adumentioning
confidence: 99%
“…The introduction of HAART has not only resulted in significant decline in mortality associated with HIV across the world, significant reduction was also seen in the prevalence of most AIDS-defining illnesses and opportunistic infections (Buchacz et al, 2010;Kaplan et al, 2000;Mocroft et al, 2004). Similarly, there has been a downward trend in the prevalence of oral opportunistic lesions in response to the use of HAART (Franceschi et al, 2008;Patton et al, 2000;Ramírez-Amador et al, 2003;Shiboski, 2002;Yang et al, 2010). Notable reduction was reported in the prevalence of two most common HIV-associated lesions, oral candidiasis and hairy leukoplakia (Eyeson et al, 2002;Nicolatou-Galitis et al, 2004;Patton et al, 2000;Ramírez-Amador et al, 2003).…”
Section: Epidemiology Of Hiv-associated Oral Manifestationsmentioning
confidence: 92%
“…Six years later, Butt et al, (2007) encountered oral manifestations with highest prevalence in the oral cavity to include: angular cheilitis 32.4%, hyperplastic candidosis (labial mucosa) 15%, erythematous candidosis (gingival) 5%, Kaposis sarcoma (hard/soft palate) 2.9% and Parotid enlargement 2%. Shiboski (2002) in South Africa reported that oral candidiasis (OC) was the most common oral lesion among HIV-infected women, and that the preliminary findings suggest that HAART is associated with a decreasing OC incidence. A study by Rwenyonyi et al, (2011) among Ugandan children living with HIV/AIDS recorded one or more oral lesions in 73% of the children examined.…”
Section: Trend Of Occurrence Of Oral Manifestations Before Arv and Dumentioning
confidence: 99%